Potential demand for a mixed public-private animal health input: evaluation of a pour-on insecticide for controlling tsetse-transmitted trypanosomiasis in Ethiopia - Swallow, B.M.; Woudyalew Mulatu; Leak, S.G.A. (Elsevier, 1995)
The new pour-on insecticides that can be used to control tsetse-transmitted trypanosomiasis confer benefits to the owners of the cattle given treatments and other people keeping cattle in areas affected by the control. A study was conducted in southwest Ethiopia to assess farmers' perceptions of the public and private benefits of the pour-on and identify the household-level factors affecting its demand. Ninety-seven percent of the 166 survey respondents had received pour-on treatments when they were free and 67 percent paid for treatments the month before the survey. Farmers noted public and private benefits from using the pour-on, the most important of which were less trypanosomiasis, fewer problems with biting flies (including tsetse), and fewer problems with ticks. The probit model estimated to quantify the effects of different variables indicates that proportions of cows and oxen, distance to the treatment centre, and seasonal factors were significant determinants of demand.